Method for preparing zif-derived porous carbon supported co / se biatomic site orr catalysts

CN117832521BActive Publication Date: 2026-10-20TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310359916.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2026-10-20
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

在以往的研究中,大多数研究都集中在双金属原子位点催化剂的构建上,而关于金属和非金属原子位点结合的双金属原子位点催化剂的报道较少

Benefits of technology

[0014]1、本发明通过调节硒含量,成功合成了一种新型的双位点电催化剂,该催化剂的Co-Nx和Se-C双位点高度分散在ZIF衍生的多孔碳骨架中。与Co-N-C和Se-N-C单位点催化剂相比,设计构建的具有Co/Se双原子位点的Co-Se-N-C催化剂在酸性电解质中的ORR性能均有显著提高,证明了Co-Nx和Se-C双原子位点的协同效应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117832521B_ABST
    Figure CN117832521B_ABST
Patent Text Reader

Abstract

The application discloses a ZIF-derived porous carbon supported Co / Se diatomic site ORR catalyst, which is prepared by the following steps: dimethyl imidazole, Zn(NO3)2.6H2O and Co(NO3)2.6H2O are reacted and dried to obtain a precursor, then the precursor is ground into powder, and the powder is put into a corundum boat, and then the powder is rapidly put into a furnace at 950 DEG C under an argon atmosphere, and the powder is rapidly heated to obtain black precursor powder, then the black precursor powder is mixed with selenium dioxide and ground into uniform powder, and the uniform powder is put into a corundum boat and placed in a tube furnace, and the powder is heated and treated under an argon atmosphere to obtain the ZIF-derived porous carbon supported Co / Se diatomic site ORR catalyst. The Co-Se-N-C catalyst prepared by the application has improved ORR performance in an acidic electrolyte, and the synergistic effect of Co-N x and Se-C diatomic sites is proved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst technology, specifically relating to a method for preparing a ZIF-derived porous carbon-supported Co / Se dual-atom-site ORR catalyst. Background Technology

[0002] Proton exchange membrane fuel cells (PEMFCs) have attracted widespread attention as one of the most promising next-generation automotive power sources. However, the slow redox reaction (ORR) at the cathode hinders the output performance of PEMFCs, requiring highly efficient ORR catalysts to achieve acceptable performance. Currently, Pt and its alloys, such as commercial Pt nanoparticles supported on carbon black, are considered ideal ORR catalysts. Nevertheless, their price and scarcity limit their widespread application. Therefore, researchers are constantly searching for inexpensive non-Pt catalysts with performance comparable to Pt. Co-based catalysts are an excellent potential alternative, but their intrinsic ORR activity is low, especially in acidic environments, resulting in insufficient improvement in the catalyst's half-wave potential and its performance in fuel cells, affecting the operation of fuel cells at higher voltages. Therefore, methods are needed to enhance the intrinsic activity of the catalytic sites, thereby increasing the operating power of fuel cells at higher voltages.

[0003] In recent years, single-atom-site catalysts have attracted increasing attention due to their fully exposed active sites, providing simple model catalysts for the study of reaction mechanisms. However, recent studies have pointed out that single-atom-site catalysts also have some drawbacks: due to the low density of active sites, they are easily occupied by intermediates, leading to severe deactivation; a single active site cannot effectively drive multi-electron and multi-proton transfer processes. To address these issues, introducing other single atoms to construct heteronuclear diatomic sites may endow catalysts with higher turnover frequencies. This strategy has great potential to overcome these shortcomings and ultimately enhance activity through tunable electronic environments and synergistic effects. As an effective way to improve intrinsic activity, bimetallic atomic site catalysts, such as Fe / Co, Fe / Mn, and Co / Mn, have recently been designed and synthesized by researchers. Compared with their corresponding single-metal active site catalysts, bimetallic atomic site catalysts exhibit higher ORR activities. In previous studies, most research focused on the construction of bimetallic atomic site catalysts, while reports on bimetallic atomic site catalysts combining metal and non-metal atomic sites are relatively few. Metals and nonmetals typically exhibit different electronic structures and physicochemical properties, and combining the two types of atoms can allow them to play different roles in catalytic reactions. Diatomic catalysts, as an extension of monoatomic catalysts, have attracted increasing attention due to their synergistic effects. However, research on diatomic catalysts is still in its early stages, primarily based on metal atom pairs. Further experimental and theoretical exploration is needed to guide the rational design of diatomic active sites. Summary of the Invention

[0004] The technical problem to be solved by this invention is to address the shortcomings of the prior art by providing a method for preparing a ZIF-derived porous carbon-supported Co / Se dual-atom-site ORR catalyst. The Co-Se-NC catalyst with Co / Se dual-atom sites prepared by this method exhibits significantly improved ORR performance in acidic electrolytes, demonstrating that Co-N... x Synergistic effect with Se-C diatomic sites.

[0005] The technical solution of this invention is: a method for preparing a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst, characterized in that: the preparation method is as follows:

[0006] Step 1: Dimethylimidazole is added to methanol and stirred until homogeneous to form solution A; Zn(NO3)2·6H2O and Co(NO3)2·6H2O are added to methanol and stirred until homogeneous to form solution B; solution B is added to A and magnetically stirred for 10 hours, then washed three times with methanol and dried to obtain the precursor; the precursor is ground into powder and placed in an alumina boat, which is placed outside the quartz tube furnace. The quartz tube furnace is heated to 950°C under an argon atmosphere, and then the alumina boat is moved into the furnace to allow the precursor powder to heat up rapidly. After holding at this temperature for 1.5 hours, it is naturally cooled to obtain black precursor powder;

[0007] Step 2: Take the precursor powder prepared in Step 1 and selenium dioxide, mix them in a certain proportion, grind them thoroughly into a uniform powder, place them in an alumina boat, put them in a tube furnace, and heat them at 5℃·min under an argon atmosphere. -1 The temperature was increased to 300℃ and held for 0.5 h, then increased to 1000℃ and held for 0 h. After natural cooling to room temperature, a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst was obtained.

[0008] Preferably, the molar ratio of dimethylimidazole, Zn(NO3)2·6H2O and Co(NO3)2·6H2O in step one is 66:15:1.5.

[0009] Preferably, in step one, the molar mass ratio of dimethylimidazole to methanol is 66 mmol: 150 mL; and the molar mass ratio of Zn(NO3)2·6H2O, the molar mass ratio of Co(NO3)2·6H2O to methanol is 15 mmol: 1.5 mmol: 100 mL.

[0010] Preferably, the drying temperature in step one is 60°C.

[0011] Preferably, the mass ratio of the Co-NC catalyst powder to selenium dioxide in step two is (0.5–4):1.

[0012] Preferably, the heat preservation time in step two is 1 hour.

[0013] Compared with the prior art, the present invention has the following advantages:

[0014] 1. This invention successfully synthesized a novel two-site electrocatalyst by adjusting the selenium content. The catalyst exhibits Co-N... x The Co-Se-C dual sites are highly dispersed within the ZIF-derived porous carbon framework. Compared to Co-NC and Se-NC single-site catalysts, the designed and constructed Co-Se-NC catalyst with Co / Se dual atomic sites exhibits significantly improved ORR performance in acidic electrolytes, demonstrating the superior performance of Co-N. xSynergistic effect with Se-C diatomic sites.

[0015] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0016] Figure 1 This is a scanning electron microscope image of the ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst prepared in Example 3 of this invention.

[0017] Figure 2 This is the structure and elemental distribution diagram of the ZIF-derived porous carbon-supported Co / Se dual-atom-site ORR catalyst prepared in Example 3 of the present invention. Detailed Implementation

[0018] Example 1

[0019] The preparation method of the ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst in this embodiment includes:

[0020] Step 1: 66 mmol of dimethylimidazole was added to 150 mL of methanol and stirred evenly for 5 min to form solution A; 15 mmol of Zn(NO3)2·6H2O and 1.5 mmol of Co(NO3)2·6H2O were added to 100 mL of methanol and stirred evenly to form solution B; solution B was added to A and magnetically stirred for 10 h, then washed three times with methanol, and dried at 60 °C to obtain the precursor. The precursor was ground into powder and placed in a corundum boat, which was placed outside the quartz tube furnace. The quartz tube furnace was heated to 950 °C under an argon atmosphere, and then the corundum boat was moved into the furnace to allow the precursor powder to heat up rapidly. After holding at this temperature for 1.5 h, it was naturally cooled to obtain black precursor powder.

[0021] Step 2: Take the Co-NC precursor powder prepared in Step 1 and selenium dioxide (SeO2), wherein the mass ratio of the Co-NC catalyst powder to selenium dioxide is 0.5:1. Mix them thoroughly and grind them into a uniform powder. Place the powder in a corundum boat and put it in a tube furnace. Incubate the furnace under an argon atmosphere at 5°C / min. -1 The temperature was increased to 300℃ and held for 0.5 h, then increased to 1000℃ and held for 1 h. After natural cooling to room temperature, a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst was obtained, and the sample was labeled Co-Se-NC-0.5.

[0022] Example 2

[0023] The preparation method of this embodiment is the same as that of Example 1, except that the mass ratio of the precursor powder to selenium dioxide in step two is 1:1. Finally, a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst is obtained, labeled as Co-Se-NC-1.

[0024] Example 3

[0025] The preparation method of this embodiment is the same as that of Example 1, except that the mass ratio of the precursor powder to selenium dioxide in step two is 2:1. Finally, a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst is obtained, labeled as Co-Se-NC-2.

[0026] Example 4

[0027] The preparation method of this embodiment is the same as that of Example 1, except that the mass ratio of the precursor powder to selenium dioxide in step two is 4:1. Finally, a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst is obtained, labeled as Co-Se-NC-4.

[0028] Comparative Example 1

[0029] The preparation method of the catalyst in this comparative example includes the following steps:

[0030] Step 1: 66 mmol of dimethylimidazole was added to 150 mL of methanol and stirred evenly for 5 min to form solution A; 15 mmol of Zn(NO3)2·6H2O and 1.5 mmol of Co(NO3)2·6H2O were added to 100 mL of methanol and stirred evenly to form solution B; solution B was added to A and magnetically stirred for 10 h, then washed three times with methanol, and dried at 60 °C to obtain the precursor. The precursor was ground into powder and placed in a corundum boat, which was placed outside the quartz tube furnace. The quartz tube furnace was heated to 950 °C under an argon atmosphere, and then the corundum boat was moved into the furnace to allow the precursor powder to heat up rapidly. After holding at this temperature for 1.5 h, it was naturally cooled to obtain black precursor powder.

[0031] Step 2: Grind the precursor powder prepared in Step 1 into a uniform powder, place it in a corundum boat, and then place it in a tube furnace. Incubate the furnace under an argon atmosphere at 5°C / min. -1 The temperature was increased to 300℃ and held for 0.5 h, then increased to 1000℃ and held for 1 h. After natural cooling to room temperature, the catalyst was obtained and labeled Co-NC.

[0032] Scanning electron microscope images of the ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst prepared in Example 3 of this invention are shown below. Figure 1The structure and elemental distribution of the prepared ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst are shown in [reference needed]. Figure 2 .

[0033] Using the ORR catalysts prepared in Examples 1-4 of this invention and the catalyst prepared in Comparative Example 1, a cathode catalyst layer and an anode catalyst layer were prepared. The preparation process of the cathode catalyst layer was as follows: 10 mg of catalyst was weighed, and 275 μL of 5 wt% Nafions, 575 μL of ethanol, and 150 μL of deionized water were added. The mass ratio of Nafions to catalyst in the catalyst slurry was 1.25. The slurry was first ultrasonicated for 15 min, then stirred in a vortex mixer for 15 min, and the ultrasonication and stirring steps were repeated a second time. 805 μL of ink was applied to a 2.01 cm² plate using a pipette. 2 On a carbon paper gas diffusion layer. Approximately 4 mg of catalyst is present per square centimeter of electrode. The preparation process of the anode catalyst layer is as follows: a 20% wt% Pt / C catalyst layer is applied to carbon paper, 10 mg of catalyst is added, along with 174 μL of 5 wt% Nafions, 626 μL of isopropanol, and 200 μL of deionized water. The loading is 0.4 mg Pt cm⁻², and the mass ratio of Nafions to catalyst is 1:1.

[0034] The membrane electrode assembly process was as follows: Nafion 117 was used as the proton exchange membrane. The prepared anode and cathode catalyst layers were pressed onto both sides of the membrane at 130℃ and 3 MPa for 2 minutes, thus creating MEAs with different cathode catalyst layers. Fuel cell experiments were conducted using an 850e fuel cell testing system (Scribner) combined with an 885 fuel cell potentiostat. In each performance-stability experiment, the H2 / O2 temperature of the fuel cell anode and cathode was humidified to 80℃. Electrochemical impedance spectroscopy (EIS) measurements were performed at a constant current of 1.0 A, with a frequency range of 0.01 Hz to 10 kHz.

[0035] The influence of the Co / Se dual sites in the catalyst prepared in this invention on fuel cell performance and the multiple effects introduced by the Se atom sites: (1) First-principles calculations show that the introduction of Se atom sites effectively regulates charge redistribution and can adjust Co-N x The electronic states of the active sites, thereby lowering the activation barrier of the rate-determining step of O2 desorption from 0.52 eV to 0.38 eV, promote charge transfer and thus improve redox reaction kinetics; the power density of the membrane electrode synthesized under the same conditions from the catalyst of Comparative Example 1 and the ORR catalyst of Example 2 increased from 228 mW / cm². -2 The ORR catalyst prepared in Comparative Example 1 was increased to 297 mW / cm². -2(ORR catalyst prepared in Example 3) The charge transfer resistance decreased from 0.507Ω (ORR catalyst prepared in Comparative Example 1) to 0.326Ω (ORR catalyst prepared in Example 3). (2) Due to the low sublimation temperature of SeO2, most of it volatilizes during calcination, leaving a rich pore structure on the catalyst. The pore volume decreased from 0.60 cm³ / s. 3 g -1 The ORR catalyst prepared in Comparative Example 1 was increased to 0.71 cm⁻¹. 3 g -1 (ORR catalyst prepared in Example 3) The porous structure is more conducive to mass transfer. (3) Se-C is conducive to the decomposition of H2O2 and the removal of free radicals. The H2O2 yield decreased from 6.7% (ORR catalyst prepared in Comparative Example 1) to 0.3% (ORR catalyst prepared in Example 3), which improved the durability of the catalyst.

[0036] The power density of the membrane electrode synthesized from the ORR catalyst of Example 1 was 242 mW / cm². -2 Charge transfer resistance 0.481Ω, pore volume 0.73cm³ 3 g -1 The yield of H2O2 was 0.75%.

[0037] The power density of the membrane electrode synthesized from the ORR catalyst of Example 2 was 254 mW / cm². -2 Charge transfer resistance 0.395Ω, pore volume 0.65cm³ 3 g -1 The yield of H2O2 was 0.47%.

[0038] The power density of the membrane electrode synthesized from the ORR catalyst of Example 4 was 285 mW / cm². -2 Charge transfer resistance 0.344Ω, pore volume 0.62cm³ 3 g -1 The yield of H2O2 was 0.68%.

[0039] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst, characterized in that: The preparation method is as follows: Step 1: Dimethylimidazole is added to methanol and stirred until homogeneous to form solution A; Zn(NO3)2•6H2O and Co(NO3)2•6H2O are added to methanol and stirred until homogeneous to form solution B; solution B is added to A and magnetically stirred for 10 h, then washed three times with methanol and dried to obtain the precursor. The precursor is ground into powder and placed in an alumina boat, which is located outside the quartz tube furnace. Under an argon atmosphere, the quartz tube furnace is heated to 950°C, and then the alumina boat is moved into the furnace to rapidly heat the precursor powder. After holding at this temperature for 1.5 h, it is naturally cooled to obtain black precursor powder; the molar ratio of dimethylimidazole, Zn(NO3)2•6H2O and Co(NO3)2•6H2O is 66:15:1.

5. Step 2: Take the precursor powder prepared in Step 1 and selenium dioxide, mix them in a certain proportion, grind them thoroughly into a uniform powder, place them in an alumina boat, put them in a tube furnace, and heat them at 5℃·min under an argon atmosphere. -1 The temperature was increased to 300℃ and held for 0.5 h, then increased to 1000℃ and held for 0 h. After natural cooling to room temperature, a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst was obtained; the mass ratio of Co-NC catalyst powder to selenium dioxide was (0.5~4):

1.

2. The method for preparing a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst according to claim 1, characterized in that: In step one, the molar ratio of dimethylimidazole to methanol is 66 mmol: 150 mL; the molar ratio of Zn(NO3)2•6H2O, the molar ratio of Co(NO3)2•6H2O to methanol is 15 mmol: 1.5 mmol: 100 mL.

3. The method for preparing a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst according to claim 1, characterized in that: The drying temperature in step one is 60 ℃.

4. The method for preparing a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst according to claim 1, characterized in that: In step two, the holding time at 1000℃ is 1 hour.

Citation Information

Patent Citations

  • Method for preparing selenium-based diatomic catalyst through high-temperature atomization method and application of selenium-based diatomic catalyst

    CN119786629A